Agar plating technique for enumeration of IL-2 producing cells in human peripheral blood mononuclear leukocytes - Hirunpetcharat C. (2014)
An agar plating technique for detection and enumeration of IL-2 producing cells from human peripheral blood mononuclear leukocytes (PBML) has been developed. This method is based on the principle that PHA-stimulated PBML, as effector cells, secrete interleukin 2 (IL-2) into soft agar containing mouse 3-day Con A blasts as IL-2 dependent responder cells. The IL-2 dependent Con A blasts proliferating around the IL-2 producing cells form colonies or clusters of cells and are easily visualized under a dissecting microscope. The development of IL-2 producing cells was optimum when 1 X 10(6) cells/ml PBML were stimulated with 2 micrograms/ml PHA-P for 4 hours, and when 2.5 X 10(5) cells were co-cultured with 6 X 10(6) Con A blasts in soft agar for 5 days. The average number of IL-2 producing cells in 10 normal healthy controls were 754 +/- 94 (mean +/- S.E.M.) cells/10(6) PBML. The numbers of IL-2 producing cells and the levels of IL-2 produced were highly correlated (r = 0.929). The subpopulation of lymphocytes in the colonies was shown to be mostly murine T-cells, since they were mostly Thy 1.2 positive, CD3 negative and surface immunoglobulin negative. This technique is very simple to perform and provides an accurate and straightforward means to enumerate IL-2 producing cells from human PBML in a variety of human immunologic disorders.